Welfare reform and social investment policy in Europe and East Asia : international lessons and policy implications - Choi, Young Jun; Fleckenstein, Timo, 1977-; Lee, Soohyun, 1977- (Bristol : Policy Press, 2021)
Providing original observations, this seminal text analyses the emergence of social investment policies in both Europe and East Asia. Experts explore the roads and barriers towards effective social investment policies, derive practical social policy implications and highlight important lessons for future social policymaking.
Title from publisher's bibliographic system (viewed on 22 Dec 2021).
Keywords: Public welfare -- Europe; Public welfare -- East Asia